2019
DOI: 10.1097/ta.0000000000002544
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid emergency room system improves timeliness of angioembolization for pelvic fracture

Abstract: BACKGROUND Timely angioembolization (AE) is known to improve outcomes of patients with hemorrhage resulting from pelvic fracture. The hybrid emergency room system (HERS) is a novel trauma resuscitation room equipped with a computed tomography scanner, fluoroscopy equipment, and an operating room setup. We hypothesized that the HERS would improve the timeliness of AE for pelvic fracture. METHODS A retrospective medical record review of patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…The creation of rapid response teams led by trauma surgery and IR, and the use of hybrid operative rooms (HORs) where available, has revolutionized the treatment of many traumatic injuries. 3,4 Many patients who were treated with surgery in the past can now be treated with expedited embolization even in hemodynamically unstable situations. Also, embolization can be a lifesaving procedure for those patients who are having uncontrollable bleeding during surgery.…”
mentioning
confidence: 99%
“…The creation of rapid response teams led by trauma surgery and IR, and the use of hybrid operative rooms (HORs) where available, has revolutionized the treatment of many traumatic injuries. 3,4 Many patients who were treated with surgery in the past can now be treated with expedited embolization even in hemodynamically unstable situations. Also, embolization can be a lifesaving procedure for those patients who are having uncontrollable bleeding during surgery.…”
mentioning
confidence: 99%
“…Regarding trauma care, several studies have reported that hybrid ER use was significantly associated with decreased time to diagnosis, improved definitive treatment, and reduced mortality. [11][12][13] The hybrid ER may also be utilized for non-trauma patients requiring a CT scan, angiography, and surgical procedures. From the perspective of life-threatening hemorrhagic shock, rAAA is similar to trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, hybrid operating room systems have to be mentioned. In multiple studies, hybrid operating rooms have been shown to improve the management and workflow in patients with severe pelvic ring injuries (36)(37)(38). Ito and colleagues recently demonstrated that the time from admission to angio-embolization was significantly shorter in the hybrid operating room group.…”
Section: Discussionmentioning
confidence: 99%
“…Ito and colleagues recently demonstrated that the time from admission to angio-embolization was significantly shorter in the hybrid operating room group. At our institution (and likely in the vast majority of trauma centers worldwide), hybrid operating room systems are currently not available, however, it would clearly pose a significant advantage in the management of these patients (38). The most commonly reported arteries that require embolization in patients with pelvic ring injuries are the internal iliac artery in approximately 67%, unnamed branches of the internal iliac artery (17%), the superior gluteal artery (4%), the obturator artery (4%), and the internal pudendal artery (3%) (39).…”
Section: Discussionmentioning
confidence: 99%